A neglected conuent middle mesial canal in an infected pretreated mandibular rst molar - A case report - Basha, Elian; Mosto, Eman (Journal of Case Reports in Dental Medicine, 2025)
In terms of root canal treatments, it is mandatory to detect all the orifices found on the pulp chamber floor to diminish the bacterial load ensuring proper chemo-mechanical debridement of the root canals and creating a three-dimensional space for an inert filling material preventing further infections; therefore, All clinicians must be aware of the Middle Mesial Canal (MMC) to provide complete cleaning and sealing of the canals, as these missing canals correlate significantly with apical periodontitis. A young female patient presented with throbbing pain and swelling on the lower left side of her face; after clinical and radiographic examinations, an infected, pretreated mandibular left first molar was found to be responsible for the symptoms. After removing the restoration and reaching the pulp chamber floor, a neglected confluent middle mesial canal was discovered, cleansed, and treated. To date, the tooth has not developed any signs of failure. Since detecting and treating all root canals in multi-rooted teeth are fundamental in terms of endodontic therapy to minimize bacterial growth, provide proper sealing of root canal systems, and increase the success rate of root canal treatments, clinicians must always have a clear conscience and take sufficient time to seek all root canals present in a tooth, not only the well-known and recurrent ones.